Foreign direct investment and exchange rates: A case study of US FDI in emerging market countries - Manop Udomkerdmongkol; Holger Görg; Oliver Morrissey (University of Nottingham, School of Economics, 2006)
This paper investigates the impact of exchange rates on US Foreign Direct Investment (FDI) inflows to a sample of 16 emerging market countries using panel data for the period 1990-2002. Three variables are used to capture separate exchange rate effects. The nominal bilateral exchange rate to the US captures the value of the local currency (a higher value implies a cheaper currency and attracts FDI). Changes in the real effective exchange rate index (REER) proxy for expected changes in the exchange rate: an increasing (decreasing) REER is interpreted as devaluation (appreciation) being expected, so that FDI is postponed (encouraged). The temporary component of bilateral exchange rates is a proxy for volatility of local currency, which discourages FDI. The results support the `Chakrabarti and Scholnick' hypothesis that, ceteris paribus, there is a negative relationship between the expectation of local currency depreciation and FDI inflows. Cheaper local currency (devaluation) attracts FDI while volatile exchange rates discourage FDI.
Keywords: 330